Penguatan Moderasi Beragama dalam Proyek Profil Pelajar Rahmatan Lil ‘Alamin Kurikulum Merdeka Madrasah - Muchamad Mufid (QuranicEdu: Journal of Islamic Education, 2023)
Cultural diversity was a necessity that Allah SWT had laid out on earth, including Indonesia. Therefore, this diversity needed to be maintained by all elements of the nation. The Religious Ministry of the Republic of Indonesia through the Independent Curriculum policy seeked to strengthen religious moderation in educational institutions. Library research (library research) was chosen in this study to examine the policy of strengthening religious moderation in the Madrasah Independent Curriculum. The results of this study indicated that strengthening religious moderation in the 2013 curriculum was still in the form of a hidden curriculum so that it needed to be developed into a curriculum in the independent curriculum. In the independent learning curriculum policy of the Ministry of Religion, strengthening religious moderation was the obligation of every school in the rahmatan lil 'alamin Student Profile strengthening project. Strengthening religious moderation through this project needed to be implemented in educational institutions.